Answer:
The given equation having only one solution i.e., "w = 3". A further explanation is provided below.
Step-by-step explanation:
The given equation is:
⇒ ![9(w-9)-2=-7w+7(w-8)](https://tex.z-dn.net/?f=9%28w-9%29-2%3D-7w%2B7%28w-8%29)
By opening the brackets, we get
⇒ ![9w-81-2=-7w+7w-56](https://tex.z-dn.net/?f=9w-81-2%3D-7w%2B7w-56)
⇒ ![9w-83=-56](https://tex.z-dn.net/?f=9w-83%3D-56)
On adding "83" both sides, we get
⇒ ![9w-83+83=-56+83](https://tex.z-dn.net/?f=9w-83%2B83%3D-56%2B83)
⇒ ![9w=27](https://tex.z-dn.net/?f=9w%3D27)
⇒ ![w=\frac{27}{9}](https://tex.z-dn.net/?f=w%3D%5Cfrac%7B27%7D%7B9%7D)
⇒ ![=3](https://tex.z-dn.net/?f=%3D3)
<span>x = number of domestic stamps
y = number of foreign stamps
Malik
collects rare stamps and has a total of 212 stamps.
=> x + y = 212
he has 34 more
domestic stamps than foreign stamps.
=> x = y + 34
which
equation represents the total number of stamps malik collected?
x + y = 212
which
equation represents the difference in the number of foreign and domestic
stamps malik collected?
x - y = 34
which system of linear equations represents the
situation?
x + y = 212
x - y = 34
</span>
Answer:
B?
Step-by-step explanation:
Well, 68% is greater than the 50% ratio of the jelly, and its also greater than C so, id have to say B.
Tell me if im wrong sorry if i am.
Answer:
For
the function f(x) is continuous on
.
Step-by-step explanation:
We have the following function
![f(x) = \left\{ \begin{array}{ll} cx^2+5x & \quad x](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cleft%5C%7B%20%20%20%20%20%20%20%20%5Cbegin%7Barray%7D%7Bll%7D%20%20%20%20%20%20%20%20%20%20%20%20cx%5E2%2B5x%20%26%20%5Cquad%20x%20%3C6%20%5C%5C%20%20%20%20%20%20%20%20%20%20%20%20x%5E3-cx%20%26%20%5Cquad%20x%20%5Cgeq%206%20%20%20%20%20%20%20%20%5Cend%7Barray%7D%20%20%20%20%5Cright.)
For the function f(x) to be continuous on
it is sufficient to have continuity at x = 6, we need to ensure that as x approaches 6, the left and right limits match, this means that
,
which holds if and only if
![c\left(6\right)^2+5\left(6\right)=\left(6\right)^2-c\left(6\right)\\36c+30=36-6c\\42c=6](https://tex.z-dn.net/?f=c%5Cleft%286%5Cright%29%5E2%2B5%5Cleft%286%5Cright%29%3D%5Cleft%286%5Cright%29%5E2-c%5Cleft%286%5Cright%29%5C%5C36c%2B30%3D36-6c%5C%5C42c%3D6)
namely if
.